Exponentially Improving the Complexity of Simulating the Weisfeiler-Lehman Test with Graph Neural Networks - Aamand, Anders; Chen, Justin Y; Indyk, Piotr; Narayanan, Shyam; Rubinfeld, Ronitt; Schiefer, Nicholas; Silwal, Sandeep; Wagner, Tal (2022)
Abstract to come...